2013
DOI: 10.1155/2013/490964
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Increases Susceptibility to Ischemic Necrosis

Abstract: Diabetic patients are at risk for spontaneous foot ulcers, chronic wounds, infections, and tissue necrosis. Current theories suggest that the development and progression of diabetic foot ulcers are mainly caused by arteriosclerosis and peripheral neuropathy. Tissue necrosis plays a primordial role in the progression of diabetic foot ulcers but the underlying mechanisms are poorly understood. The aim of the present study was to investigate the effects of hyperglycemia per se on the susceptibility of ischemic ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 32 publications
1
23
1
3
Order By: Relevance
“…Various studies have demonstrated controversial results, of which some reported that probiotic supplementation significantly reduced lipid profiles, while some studies did not report any improvements in lipid profiles . Hyperglycaemia and hyperinsulinemia are associated with an acceleration of arteriosclerotic and atherosclerotic changes of the greater arteries resulting in the decreased blood flow, further contributing to a limb‐threatening ischemic condition . Therefore, improvement in glucose metabolism has been suggested as an effective means to delay vascular complications in DFU subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated controversial results, of which some reported that probiotic supplementation significantly reduced lipid profiles, while some studies did not report any improvements in lipid profiles . Hyperglycaemia and hyperinsulinemia are associated with an acceleration of arteriosclerotic and atherosclerotic changes of the greater arteries resulting in the decreased blood flow, further contributing to a limb‐threatening ischemic condition . Therefore, improvement in glucose metabolism has been suggested as an effective means to delay vascular complications in DFU subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant change in glucose and insulin concentrations was seen after zinc supplementation (240 mg/day of zinc as zinc gluconate) among patients with T2DM with normal zinc levels for 3 months . Hyperglycemia and insulin resistance are associated with an acceleration of arteriosclerotic changes of the greater arteries resulting in decreased blood flow, further contributing to a limb threatening ischemic condition . The diabetic dyslipidemia is one of several factors that contribute to developing macrovascular disease in diabetic patients .…”
Section: Discussionmentioning
confidence: 99%
“…As described previously, 17 through a longitudinal incision in the inguinal region that has been shaved, the femoral artery was dissected down to popliteal artery and resected in the left limb (ischemic limb) while conserved in the control right limb (nonischemic limb). After the arterial lesion, wounds were created on both legs on the dorsal aspect of the both feet in all animals by removing a full-thickness skin area of 1.2 × 0.8 cm (Fig.…”
Section: Methodsmentioning
confidence: 99%
“… 9 , 10 By contrast, the role of hyperglycemia per se is not well elucidated and remains controversial. 3 , 11 , 12 Clinical studies reported that hyperglycemia may interfere with ischemia and adversely affect the outcome of ischemic insults, 13 17 but this interaction has not been investigated in wound repair yet.…”
mentioning
confidence: 99%